Specific characteristics of immunohistochemical changes of the cellular infiltrate (the content of mucins MUC 2, 3, 4) in the mucous tunic of the bronchi in patients with chronic obstructive pulmonary disease - S. V. Kovalenko; A. E. Dorofeev; I. V. Vasilenko; I. S. Davidenko (Zaporozhye State Medical University, 2013)
Introduction. Changes of the mucin expression by the competent cells of the bronchial mucous membrane (MM) and dyscrinia are the common evidence of the inflammatory process in case of chronic obstructive pulmonary disease (COPD) that logically substantiates the importance for the investigation of the mucin influence on the progression processes of the inflammation in the airways tract (AW). Purpose of the research. A complex study of the immunohistochemical changes of the cellular infiltration according to the mucin content MUC 2, 3, 4 in the mucous membrane of the bronchi at different variants of COPD exacerbation. Materials and Methods. An analysis of 30 case histories of patients with exacerbation of COPD undergoing inpatient treatment at the department of pulmonology was carried out. With the object of determining the degree and character of bronchial inflammation fibrobronchoscopy was carried out in all patients by means of Olympus fibrobronchoscopy. Intravital biopsy of the bronchial MM according to generally accepted technique was performed in connection with a necessity of preserving integrity of antigens in the bronchial structures for immunohistochemical investigations. For the first time an immunohistochemical study of the expression of mucin has been carried out by means of primary monoclonal antibodies to the antigens of proteins MUC-2, MUC-3, MUC-4 in the integumentary epithelium, goblet cells, the epithelium of the mucous glands and the fusiform cells of the stroma of the mucous tunic of the bronchi in patients with chronic obstructive pulmonary disease (COPD) during an infectious and noninfectious exacerbation. Results of the research. It has been established that during an exacerbation of chronic obstructive pulmonary disease in different types of epithelial cells of the mucous tunic of the bronchi a decline of the expression of antigens of MUC2 and MUC3 of a various degree of a marked character occurs. Synthesis of MUC 2 and MUC 3 decreases in the respiratory tract at infectious exacerbation of COPD in comparison with their expression at noninfectious exacerbation of COPD in all structures except fusiform cell of the stroma-fibroblasts. In our opinion a decrease of the mucin expression at the infectious exacerbation of COPD, most evident in the tegmental epithelium, the epithelium of the mucous glands and less in goblet cells can be explained by the influence of pathogenic microbes present in a great number on the mucous membranes and tegmental epithelium of the bronchi at infectious exacerbation of COPD. Even expression of MUC 2,3, which appears in fibroblasts of the stroma and does not depend on the variant of exacerbation of COPD is probably connected with the phenomena of an epithelial-mesenchymal transformation (EMT), when normal epithelial cells (for example, of the mucous membrane of the glands) under the influence of certain factors, for instance, TGFβ1, obtain the features of miofibroblast cells. Owing to the EMT the epithelial cells are losing intercellular ties, move to the interstitium, where obtaining a complete mesenchymal fenotype, take part in the synthesis of fibrous matrix. Conclusions. The expression of antigens MUC2 and MUC3 detected in the fusiform cells of the stroma (fibroblasts) during a COPD exacerbation enables to certify a fact of an epithelial-mesenchymal transformation, namely, a change of transformed epithelial cells, as a result of which they react differently than ordinary epithelial cells to molecular factors which play a certain role in the development of an inflammatory process and progression of fibrosis in COPD.